Competitiveness and urban prosperity in Mexico: their contribution to quality of life - Salas Durazo, Iván Alejandro; Rivas Jiménez, Claudia Patricia; Soria Romo, Rigoberto (Economía Sociedad y Territorio, 2025)
This paper seeks to identify the relationship between urban competitiveness and prosperity in 70 Mexican cities taking as a reference its contribution to the quality of life. To estimate urban competitiveness, a regression model was developed with a data panel based on the variables used by the Instituto Mexicano para la Competitividad (IMCO, 2010-2018); and the indexes of prosperous cities from UN-Habitat (2015 and 2018). The main result reaffirmed the importance of public policies as an articulating element between competitiveness and urban prosperity through economic promotion policy and social policy as instruments to improve quality of life.